2005
DOI: 10.1002/adma.200401960
|View full text |Cite
|
Sign up to set email alerts
|

Robust, Non‐Cytotoxic, Silica‐Coated CdSe Quantum Dots with Efficient Photoluminescence

Abstract: Near-monodisperse semiconductor quantum dots (QDs) have been synthesized by wet-chemical methods for fluorescent biological labels [1±5] and light-emitting devices.[6±8] Organic capping of QDs with surfactants can provide electron passivation and form a barrier against aggregation of crystallites. Typically, CdSe QDs capped with trioctylphosphine oxide (TOPO) have a quantum yield (QY) of~10 % at room temperature. [9] Coating of CdSe QDs with semiconductors of larger bandgaps (such as ZnS) has been shown to im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
386
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 466 publications
(392 citation statements)
references
References 32 publications
(39 reference statements)
6
386
0
Order By: Relevance
“…[139,140] The problem of acute toxicity and photo-oxidation can be overcome by capping with a protective shell of insulating material or semiconductor, for example, ZnS-coated CdSe core/shell QDs. [141] As water solubility is key to their applications in imaging, there are a range of methods reported to make the QDs water soluble and biocompatible for biological imaging, such as fabricating the surface with suitable thiolated ligand, [142] over-coating with silica, [143,144] and encapsulating with amine-modified polymer. [145] Likewise, there are a number of strategies for their functionalization.…”
Section: Optical Imagingmentioning
confidence: 99%
“…[139,140] The problem of acute toxicity and photo-oxidation can be overcome by capping with a protective shell of insulating material or semiconductor, for example, ZnS-coated CdSe core/shell QDs. [141] As water solubility is key to their applications in imaging, there are a range of methods reported to make the QDs water soluble and biocompatible for biological imaging, such as fabricating the surface with suitable thiolated ligand, [142] over-coating with silica, [143,144] and encapsulating with amine-modified polymer. [145] Likewise, there are a number of strategies for their functionalization.…”
Section: Optical Imagingmentioning
confidence: 99%
“…Cd). In addition, silica is a relatively biocompatible material and its surface can be easy functionalized, which makes QDs@SiO 2 suitable for bioconjugation [15,16]. The third approach is based on encapsulation of the hydrophobic nanoparticles in different carrier vehicles e.g.…”
Section: Hydrophilization Of Qdsmentioning
confidence: 99%
“…Liposomes, which are spherical lipid vesicles, can also be used for encapsulation. Their hollow spherical structure and high loading capacity makes them attractive carriers for hydrophobic QDs [15,19,25]. It was shown that encapsulation of QDs into liposomes provides transfer of waterinsoluble QD into aqueous media, facilitates their bioconjugation with proteins, minimizes nonspecific interaction of water-soluble and water-insoluble QD with surface material, and amplifies the analytical signal [2].…”
Section: Hydrophilization Of Qdsmentioning
confidence: 99%
“…Many researchers demonstrated that QDs' toxicity depends on multiple factors derived from individual QDs' physicochemical properties such as QDs size [7,8] , charge [9] , stability [10] , coating [11,12] , and ingredients [13] . Derfus et al [14] concluded that QDs' toxicity was directly correlated to the release of the heavy metal ion (Cd 2+ ) derived from the oxidation of capping materials.…”
Section: Introductionmentioning
confidence: 99%